(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Cytomegalovirus infection (CMVI), cytomegaly - an infectious disease caused by the herpesvirus cytomegalovirus type 5, characterized by polymorphic clinical signs and a specific morphological picture. CMV is the most common causative agent of congenital infection.[2]